Application of Text File Steganography on Video using Least Bit Significant (LSB) Method - Mellynda, Nabila; Nasution, Yusuf Ramadhan (Sistemasi: Jurnal Sistem Informasi, 2024)
In the era of rapid development of information technology, data security is a crucial aspect that must be considered. The transfer and storage of information involves various media, including text and video. Unfortunately, most data sent or stored tends to be vulnerable to security threats. The purpose of this research is to implement text file steganography on video using the Least Bit Significant (LSB) method that can be used to hide secret messages. The method used in this research are LSB and Waterfall development method. The results of the study concluded that the LSB algorithm can be used in the process of insertion and extraction of text messages on video, text messages in this study are text contained in a text file with the txt extension. Videos that have been inserted text messages will have an extension of mp4 and cannot be played on video file playback media, The application produced in this study can be run through a web browser application, The application in this study was built using Visual Studio Code software using the HTML and Javascript programming languages.